Ferramenta computacional para gestão da manutenção de transformadores a óleo - Carlos, Vinicius Hammoud (2018)
This work shows the creation of a program on Java language for the management of the maintenance processes of oil transformers, where from the insertion of done maintenance tests’ data, it is possible to know the conditions of the analyzed transformer simply and quickly. The creation of the computational tool considers noise tests, visual inspection, physico-chemical tests, chromatographic tests, insulation resistance tests, transformation ratio measurement test, bushing power factor test, temperature measurements of the winding and temperature measurements of the oil. Still, it is possible with this computational tool to draw up a maintenance schedule in periods of less than six months, semiannual, annual and five-year periods. The program takes care of storing all maintenance data carried out in a database. In this work, the efficiency of the management program is tested using data from maintenance reports of oil transformers, comparing the results obtained in the use of the program with the result found in these maintenance reports.